719–759: The Chronicon Anianense on the Beginning and End of Muslim Rule over Septimania (Transmediterranean History, 2020)
The article deals with the beginning and end of Muslim rule over Septimania in the eighth century from the perspective of a chronicle, which in its original form was probably produced within the confines of the temporal and spatial events which it describes. The article examines the degree to which the Muslim conquerors established their rule in south-western France and why the Carolingians then subjugated the region in a process of conquest that lasted almost three decades. The Muslim-Frankish conflicts are not interpreted as an expression of a religiously motivated "clash of civilisations," but as a military confrontation between two expanding spheres.
Keywords: Carolingians; Septimania; Arabic-Islamic expansion; border zone; settlement; war; Christians under Muslim rule; Franks; Visigoths